FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN DAGING SAPI DI INDONESIA - Fatmawati, Fatmawati; Rostin, Rostin; Baso, Jamal Nasir (JURNAL EKONOMI UHO, 2016)
The purpose of this study was to determine the factors that affect the demand for beef in Indonesia. This study uses secondary data with the time series 1999-2014 period. The data obtained from the Central Bureau of Statistics and Department of Agriculture. The analytical is used multiple regression analysis. The study concluded that consumption and income significant influence demand of beef, but beef of production variable not significant. This indicated that Indonesian depend on impor of beef from the other country. Beside that, demand of beef able to be explained amounted to 93,3 percent by production of beef, beef consumption, and incomes variable; and the remaining 6.7 percent is explained by other factors.